Fungitoxicity of plant extracts against Sclerotinia rot of Indian mustard incited by Sclerotinia sclerotiorum - RAM PHOOL GHASOLIA, SURESH MEENA and ARJUN LAL YADAV, JITENDRA SHARMA*, SHAILESH GODIKA (Indian Phytopathology, 2016)
Sclerotinia rot of mustard incited by Sclerotinia sclerotiorum (Lib.) de Bary. is a major disease of Indian mustard. Disease management with chemicals is economically not viable and also not safe for the environment. Therefore, the present investigations aimed to carry out the test of plant extracts against S. sclerotiorm under in vitro and in vivo conditions. The fungitoxicity of plant extracts was tested in vitro (by poisoned food technique and in vivo against S. sclerotiorum. Among plant extracts, garlic clove extract was found most effective in inhibiting mycelial growth (39.66, 61.55 and 76.33%) of S. sclerotiorum at 5, 10 and 15 per cent, respectively followed by safeda leaf extract(13.0, 33.77 and 53.33 %) over control. The plant extracts were tested in vivo by applying as seed application, foliar application and seed - cum - foliar application. Garlic clove extract was found most effective in reducing the disease intensity followed by safeda.